(untitled) (Proceedings OPTIMAL, 2025)
Narcotic abuse leads to physiological disorders characterized by increased cortisol levels in response to stress. Rehabilitation is an important process in the recovery of narcotic abusers. Serum cortisol levels are used as an indicator of increased physiological stress in the early stages of rehabilitation due to withdrawal stress and tend to decrease as rehabilitation progresses. This study aims to determine the effect of rehabilitation duration on serum cortisol levels in drug-abusing patients at Mutiara Sukma Psychiatric Hospital. The design used is an observational analytical study with a cross-sectional approach. The sample consisted of 28 patients divided into two groups: 13 patients in the detoxification group (2–14 days) and 15 patients in the social rehabilitation group (45–134 days). Cortisol levels were measured using the ELISA method, and data analysis was performed using the Mann-Whitney U test. The results showed that cortisol levels in the detoxification group ranged from 63.20 to 217.78 ng/mL (mean 114.07 ng/mL), while in the social rehabilitation group, they ranged from 16.63 to 59.45 ng/mL (mean 38.89 ng/mL). Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant difference. Lower cortisol levels in the social rehabilitation group reflect reduced physiological stress and improved stability of the neuroendocrine system, supported by a stable rehabilitation environment, continuous social support, and long-term psychological interventions that contribute to the normalization of hypothalamic pituitary adrenal (HPA) axis function.